Internal Carbon Pricing: a lever for corporate decarbonization or checking the box on climate disclosure? - Benedicto, Sofia Cristina Lopes (2022)
Companies are being pressured to accelerate their climate change mitigation efforts and among the actions being taken is the adoption of an internal carbon price (ICP), used for financial modeling and regulatory risk management or as an incentive for cutting emissions. However, the literature on voluntary disclosure and environmental performance suggests that claims regarding climate action might be a tool for legitimacy and not necessarily represent the actual practice. This raises the question: are the reports of ICP adoption a mere reflection of companies appearing to be what stakeholders expect on their climate disclosure? Or is ICP an effective lever for corporate decarbonization? The present work addresses a research gap, investigating the effect of internal carbon pricing on absolute emissions and examining the influence of different types of ICP. This quantitative research uses secondary data licensed from CDP originally collected between 2015 and 2021.The sample is composed of 1337 companies from 54 countries and from the industries of Materials, Manufacturing and Power generation. The investigation is conducted in three parts: initially the cross-sectional dataset is examined using categorical variables only; in a second step, the data is filtered for the relevant control factors revealed by the first analysis, and emissions from companies with similar profile are compared; lastly, the dataset is organized into a longitudinal unbalanced panel and analyzed for statistical differences in Scope 1 emissions. The results indicate an association between adopting ICP and reporting absolute emission reduction. Furthermore, one type of ICP is found more closely associated to decarbonization, which represents a novel finding suggesting that how ICP is implemented affects the significance of correlation between variables. The investigation concludes that for power generation companies with operations in carbon-regulated markets, those that adopt ICP achieve deeper level of decarbonization.